The Case For a Humanistic Poetics - Schwarz, Daniel R. author. aut Link
XI, 215 p.
Keywords: An attempt to define a humanistic and pluralistic ideology of reading which takes recent theory into account. By the same author as "The Humanistic Heritage: Critical Theories on the English Novel from James through Hillis Miller", and "Reading Joyce's `Ulysses'".